Avaliação em educação física escolar na rede municipal de Vila Velha/ES: proposta de intervenção - Izoton, Gabriel Pavesi (2023)
The study had as its theme the evaluation in School Physical Education and the objective of carrying out an evaluative project that would provide subsidies on the students' learning in the most diverse dimensions of knowledge, such as: attitudinal, emotional, procedural and conceptual. This project was carried out with the 1st and 5th grade classes of the Municipal Elementary School Rubem Braga, located in the municipality of Vila Velha, Espírito Santo, Brazil. The methodology used was qualitative and evaluation. We used three instruments in the “formal evaluation” (VILLAS BOAS, 2006), a box with emoticons, in which the students filled in at the end of each class, a box with 7 criteria for the teacher to analyze the students who are: 1) understands what It was asked; 2) has difficulty performing the activity; 3) has good behavior with colleagues; 4) respects the rules of activities; 5) preserves school material and spaces; 6) has initiative during activities; 7) has difficulty executing movements and the test, which was carried out every fourth class in small didactic units. We also used the “informal evaluation” (VILLAS BOAS, 2006), made through daily contact with students without them knowing they were being evaluated. We found that the evaluation project gave us enough subsidy to state that the students achieved the objectives set, began to understand the real meaning of evaluation and had more autonomy in their teaching/learning/evaluation process. We also concluded that it is difficult to assess students without imposing a grade.